MPS reveals isometric PCR artefacts in degraded samples. Issue 1 (December 2019) - Fattorini, Paolo; Pogorelc, Barbara Gornjak; Cilieri, Solange Sorcaburu; Zupanc, Tomaž; Previderè, Carlo; Pajnič, Irena Zupanič
Abstract: It is well known that DNA damage promotes PCR artefacts. In addition, as MPS provides the most accurate typing of PCR products, this technology should be able to highlight more PCR artefacts than the conventional CE approach. To test this hypothesis, a DNA sample was degraded by heating at 70 °C for 8, 16 and 24 h. The three resulting samples #1, #2 and #3 and the untreated control sample were then analysed by the Precision ID Globalfiler NGS STR Panel v2, in duplicate tests. The data analysis was performed by the Converge v2.1 software using the default setting parameters. Artefacts were identified only in the degraded samples #2 and #3. Few well known artefacts (allelic imbalance, stutter products and allelic drop out) and several drop in phenomena were flagged by the software. The majority (18 out 22) of these drop ins were sequenced as "isometric artefacts", e.g. PCR artefacts which cannot be identified by the employment of CE. The molecular features of these PCR artefacts, as well as their risk to be confused with a DNA mixture, are described.